2022
DOI: 10.1186/s12877-021-02727-4
|View full text |Cite
|
Sign up to set email alerts
|

What constitutes ‘good’ home care for people with dementia? An investigation of the views of home care service recipients and providers

Abstract: Background Our objective was to explore what people receiving and providing care consider to be ‘good’ in-home care for people living with dementia. Methods We conducted 36 in-depth interviews and two focus groups with key stakeholders in Australia in the first quarter of 2018. Participants included those receiving care (4 people living with dementia, 15 family carers) or providing care (9 case managers, 5 service managers, 10 home care workers). Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Continuous education for all staff is also called for, where ethical issues also need to be discussed (SOU, 2021: 52). Goh et al (2022) found that, beyond education, good communication between the employer and the employee is needed regarding, for example, the information that the staff receives about the person they are going to help. If staff receive too little information, they do not know what is expected of them except for specific tasks to be completed.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous education for all staff is also called for, where ethical issues also need to be discussed (SOU, 2021: 52). Goh et al (2022) found that, beyond education, good communication between the employer and the employee is needed regarding, for example, the information that the staff receives about the person they are going to help. If staff receive too little information, they do not know what is expected of them except for specific tasks to be completed.…”
Section: Discussionmentioning
confidence: 99%
“…Good training is essential for homecare, not only to drive‐up quality but also to promote the welfare and social status of its workers. It is internationally recognised that training requirements in homecare lack rigour (Goh et al, 2022 ; Leverton et al, 2021 ). Some evidence links poor training as a characteristic trait of ‘dirty work’ occupations (Hansen, 2016 ) with the prospect that improved standards of learning may improve recruitment and retention and provide a more positive occupational identity (Clarke & Ravenswood, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies have identified elements considered to be important for "good" home care for people living with dementia [11,[15][16][17]. These elements include the availability of formal home care services and support, in addition to the perceived knowledge, security and dignity needed to care for a person with dementia [11,15].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, studies have identified elements considered to be important for "good" home care for people living with dementia [11,[15][16][17]. These elements include the availability of formal home care services and support, in addition to the perceived knowledge, security and dignity needed to care for a person with dementia [11,15]. While few frameworks for quality dementia home care exist for use in general health settings [18], Forbes and colleagues (2008) previously identified the availability and acceptability of formal services as central to positive home and community care experiences.…”
Section: Introductionmentioning
confidence: 99%